Synthesis of new asparagine-based glycopeptides for future scanning tunneling microscopy investigations - Sršan, Laura; Ziegler, Thomas (Beilstein Journal of Organic Chemistry, 2020)
For investigations on the biological functions of oligosaccharides and peptidomimetics, new asparagine-based mono- and disaccharides containing glycopeptides were prepared in solution. The applicability of two common peptide coupling reagents, using an orthogonal Fmoc/t-Bu strategy along with acetyl protecting groups for the carbohydrate moiety, was studied. Thus, the prepared libraries of glycopeptides were designed as model systems of cell surfaces for future investigations by combined preparative mass spectroscopy and scanning tunneling microscopy (STM) using soft-landing electrospray beam deposition (ES-IBD), on metal surfaces.
Keywords: amino acids; asparagine; carbohydrates; glycopeptides; peptidomimetics